Determining factors of environmental concern in purchasing decisions - Oliveira Júnior, Jonilson Carvalho de (2020)
Goal: Identifying the determining factors of concern with the environment in the purchasing decisions from the users’ perspective in the digital social media network.Method: The research sample consisted of 288 individuals. The questionnaire was the data collection tool with 26 questions. The analysis method was the mean descriptive analysis and construct variable standard deviation, and the exploratory factor analysis, both developed by the SPSS software, version 12.Originality/Relevance: In order for the companies to meet the consumers’ expectations, from sustainable companies engaged with social and environmental causes, and thus create competitive advantages, it is of fundamental importance that they know which environmental factors the consumers take into account in order to define their purchases.Results: The research results pointed to the existence of 4 determining factors concerning the environment in the research individuals’ purchase decisions, enabling a better understanding of sustainable consumption behavior.Theoretical/methodological contributions: The results of the study contribute to the formation of a more solid theoretical approach to analyze and understand the determinants of the concern with the environment in purchasing decisions.Social/practical contributions to management: The aim is to provide companies with a better outline of the determining factors of concern with the environment in purchasing decisions, which in possession of such information, will be able to develop more assertive strategies in meeting the demands of this public, boosting their sales, as well as contributing to the solidification of sustainable development.